Pengembangan Peternakan dan Pemanfaatannya Sebagai Hewan Kurban Desa Mangli Kediri - Yuni Kurniati; Anni Rahmat; Roostikasari Nugraheni; Ahmad Dahlan Malik (LPPM Universitas Trunojoyo Madura, 2022)
Puncu District is one of the 26 sub-districts in Kediri Regency. The majority of the residents' livelihoods are farmers, farm laborers, and ranchers. Residents who have livestock as a source of income other than the agricultural business sector, on average, still apply conventional maintenance patterns. Sacrifice is a teaching that is almost unified in terms of the time of its implementation with the pilgrimage. However, it differs in terms of the place and the perpetrators. Sacrifice is usually performed during Eid al-Adha. The celebration of Eid al-Adha is accompanied by the slaughter of sacrificial animals which are carried out simultaneously. There are several problems in the management of livestock, one of which is regarding the management of livestock which is still not good and the livestock production is not optimal. Livestock management in this case is all aspects that affect livestock business, such as: nutrition for animal feed, cage construction, cage sanitation, maintenance methods, vaccination or treatment programs, seed selection, to livestock production and reproduction factors. This activity is carried out in the form of a fostered village with several activities such as counseling, survey of livestock, and distribution of sacrificial animals. With this service activity in the form of a guided village, it is hoped that it will be able to develop management of goat farm management, starting from livestock seeds to the process of selling and distributing livestock as sacrificial animals.